Perceptions of organizational culture and board effectiveness on Malaysian cooperative board of directors - Mohd Hashim, Hezlina; Abdul Latiff, Ahmed Razman (Human Resource Management Academic Research Society, 2019)
This paper is a pilot study that examines the relationship between organizational culture and board effectiveness in cooperative movements. Past studies have shown that organizational culture has influence on performance but there have been very limited studies on its impact on cooperative’s board effectiveness. This study aims to examine the impact of organizational culture on Malaysian cooperatives board of directors’ effectiveness. The study adopted the survey research design while the population of the study is all board of directors in Malaysian cooperative movements. The study found a significant relationship between organizational culture and board effectiveness in cooperative movements and concludes that organizational culture is very important to enhance organizational performance of the cooperatives.